Influence of Technological Factors on the Maximum Allowance for Machining of Flat Surfaces of Blanks of Parts of the Type “Flange” - Derybo, O. V.; Dusaniuk, Zh. P. (Visnyk of Vinnytsia Politechnical Institute, 2019)
There has been considered an important stage in the design of technological processes for the manufacture of machine parts - the choice of allowances for machining, namely, the determination of maximum allowances, since the quantitative values of maximum allowances are needed to choose the size of the machine according to the power of the motor of the main drive and to determine the necessary clamping forces of the devices for the installation of machined blanks. In order to find out the influence of technological factors on the magnitude of the maximum allowances for the processing of flat surfaces of parts of the “Flange” type, a device for dimensional analysis of technological processes using the theory of graphs was used. For a part of the “Flange” type, a route for machining, a dimensional flow diagram and a graph of technological dimensional circuits have been developed. On the basis of this graph, the equations of technological dimensional chains and the formula for determining the maximum allowances are found. As a result of the analysis of these equations, it was revealed that the tolerances of the size of the original workpiece and their arrangement are influenced substantially by the magnitudes of the maximum allowances for the preliminary and one-time processing. It is shown that in order to reduce the maximum allowances for the treatment of planes (faces), it is necessary to set the axial dimensions of the initial workpiece relative to one measuring base and, accordingly, to provide the necessary precision of these dimensions in the manufacture of the workpiece. The results of the work can be useful in designing the technological processes of mechanical processing in the machine-building industry and in the training process.